Development of engineered Candida tropicalis strain for efficient corncob-based xylitol-ethanol biorefinery - Anup Kumar Singh; Farha Deeba; Mohit Kumar; Sonam Kumari; Shahid Ali Wani; Tanushree Paul; Naseem A. Gaur (Microbial Cell Factories, 2023)
Abstract Background Xylitol has a wide range of applications in the pharmaceuticals, cosmetic, food and beverage industry. Microbial xylitol production reduces the risk of contamination and is considered as environment friendly and sustainable compared to the chemical method. In this study, random mutagenesis and genetic engineering approaches were employed to develop Candida tropicalis strains with reduced xylitol dehydrogenase (XDH) activity to eliminate co-substrate requirement for corn cob-based xylitol-ethanol biorefinery. Results The results suggest that when pure xylose (10% w/v) was fermented in bioreactor, the Ethyl methane sulfonate (EMS) mutated strain (C. tropicalis K2M) showed 9.2% and XYL2 heterozygous (XYL2/xyl2Δ::FRT) strain (C. tropicalis K21D) showed 16% improvement in xylitol production compared to parental strain (C. tropicalis K2). Furthermore, 1.5-fold improvement (88.62 g/L to 132 g/L) in xylitol production was achieved by C. tropicalis K21D after Response Surface Methodology (RSM) and one factor at a time (OFAT) applied for media component optimization. Finally, corncob hydrolysate was tested for xylitol production in biorefinery mode, which leads to the production of 32.6 g/L xylitol from hemicellulosic fraction, 32.0 g/L ethanol from cellulosic fraction and 13.0 g/L animal feed. Conclusions This work, for the first time, illustrates the potential of C. tropicalis K21D as a microbial cell factory for efficient production of xylitol and ethanol via an integrated biorefinery framework by utilising lignocellulosic biomass with minimum waste generation.